THE ANALYSIS OF SCIENTIFIC COMMUNICATION PATTERN IN HIGH SCHOOL BIOLOGY CLASS - Itsnaini, Susana Mega; Muzzazinah, Muzzazinah; Ramli, Murni (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
ANALISIS POLA KOMUNIKASI SCIENTIFIC PADA PEMBELAJARAN BIOLOGI SEKOLAH MENENGAH ATAS Abstract This research aims to study (1) the pattern of scientific communication in biology classes, and (2) the factors and reasons hinder the communication process during the learning process. This is a classroom observation conducted in two classes of grade XI Science of Gondangrejo High School, which were selected randomly. Fifty-five students participated, and two biology teachers had also been involved. The pattern of scientific communication was analyzed based on 10 times observations of both classes, then all communications recorded and analyzed based on VICS Flanders. The hindrances of communication were checked based on categorization introduced by Lunenburg, which consists of four: process, physics, semantic, and psycho social. The findings of the research shows that the pattern of communication is mostly balance between teacher and students, which is represented by region C G J K L M P R (52.43%). Whilst, the area of teacher's domination is 24.79% (A B D E F H I ), and the area of student’s domination scores 22.78% (N O S T). The pattern of scientific communication is two ways communication between teacher and students, but the frequency of student to initiate the communication remains low. The factors hinder the communication process are process barriers. Abstrak Penelitian ini bertujuan mengetahui (1) pola komunikasi scientific pada pembelajaran biologi; (2) penyebab kendala komunikasi di kelas biologi. Penelitian ini adalah penelitian observasi kelas, yang dilakukan di dua kelas XI IPA SMA Negeri Gondangrejo yang dipilih secara acak. Siswa yang terlibat sejumlah 55 siswa, dan dua orang guru biologi juga menjadi partisipan. Data penelitian adalah proses komunikasi di dalam kelas yang diperoleh dari hasil observasi pembelajaran di dua kelas selama 10 kali kemudian seluruh komunikasi direkam dan dianalisa berdasarkan VICS Flanders. Kendala komunikasi dianalisis berdasarkan kategorisasi menurut Lunenburg (2010) yang terdiri 4 kategori, yaitu proses, fisik, semantik, dan psikososial. Hasil penelitian menunjukkan bahwa pola komunikasi yang terjadi adalah pola komunikasi seimbang antara guru dan siswa, dibuktikan dengan persentase wilayah C G J K L M P R (52.43%). Adapun persentase wilayah dominasi guru adalah 24.79% (A B D E F H I), dan presentase dominasi siswa adalah 22.78% (N O S T). Pola komunikasi scientific yang terbentuk merupakan komunikasi dua arah, tetapi menunjukkan inisiasi komunikasi scientific siswa rendah. Kendala berkomunikasi di kelas umumya disebabkan oleh hambatan psikososial. Permalink/DOI: http://dx.doi.org/10.15408/es.v10i1.6834